Implementation of a Fault-Tolerant AC/DC Converter for Permanent Magnet Synchronous Motor Drive Systems - Liu, Tian-Hua; Wang, Yu-Wei (Frontiers in Electronics, 2021)
Fault tolerant drive systems have played an increasing role for electric vehicles and elevators in order to improve reliability, availability, and maintenance. For safety reason, a fault-tolerant drive systems and redundant devices are required to be integrated with the traditional motor drive systems and execute real-time fault detection, diagnosis, isolation, and control to make sure the fault-tolerant drive system can operate normally although some faults happen. In this paper, an AC/DC converter faults, which includes a single-phase rectifier diode faulty, a three-phase full-rectifier diode faulty, and a DC-link capacitor faulty are investigated. The research includes fault detection, fault diagnosis, fault isolation, and fault control to improve the reliability of the drive system and reduce current harmonics. A digital signal processor, manufactured by Texas Instruments, TMS320F2808 is used as a control center to achieve the fault tolerant. Experimental results validate theoretical analysis to demonstrate the correctness and feasibility of the proposed methods. The proposed method can be easily implemented in industrial products due to its simplicity.